Proposed Marketing Strategy for Two Hands Full Café - Saputra, Stefen Lili; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract - Indonesian local coffee consumption is rising about 7,5% per year. This indicates that Indonesian local people are becoming more familiar with the habit of consuming coffee. The lifestyle of coffee consuming now makes some people pay more attention to the quality of the coffee that they drink. Two Hands full is a specialty coffee shop established in November 2013. The idea is to be specialty coffee shop with specialty on providing mostly coffee based beverages. Two hands full main concept is simply a combination of specialty coffee, all-day breakfast menu, and cool design. The café has been running for five months, and the main issue that needs to be resolved is to reach more customers. This research goal is to formulate marketing strategies for Two Hands Full café based on the current condition of Two Hands Full and the consumer behavior. From the exploration, it is found out that the root cause of the business issue in Two Hands Full is the lack of awareness of consumer responds and needs. The exploration of consumer responses is determined trough questionnaire. The research shows that every element of marketing mix affects the customer in their purchase and post purchase behavior. The research shows customer responses about marketing mix expectation and also behavioral tendencies that can help Two Hands Full in creating more effective marketing strategies. Priority order for marketing mix elements based on customer response is : place, product, promotion, price, process, people, and physical evidence.. Proposed 7P marketing mix strategies for Two Hands Full : promote specialty menu, new menu design, standard menu presentation, psychological pricing strategy, bicycle discount, meal packages, online promotions, word of mouth activation, direct customer seating, regular staff training, making staff SOP, change some chair, make signage. The marketing strategies will be applied in structured implementation plan. The implementation plan will begin in June 2014 until May 2015. The implementation plan describes about the timeline of every marketing strategies.Key words : Coffee, Marketing Strategy, Consumer Behavior, Marketing Mix